Advancements in alternative approaches to address antimicrobial resistance in bacterial pneumonia: a comprehensive review - Daraghmeh, Dala N.; AbuIriban, Roaa Waleed; Nawawreh, Nour; Abuamro, Ansam Mahmoud; Alassar, Momin M.; Daraghma, Salahaldeen N.; Alhajahmed, Nesma M.; Thandar, Yasmeen (Frontiers in Microbiology, 2025)
PurposeThis review explores both current and emerging alternative treatment approaches to combat AMR specifically in the context of bacterial pneumonia, highlighting therapies that extend beyond conventional antibiotics.MethodsPubMed, Embase, and Google Scholar were searched for full-text, English-language articles, with emphasis on publications from 2020 to 2025. Earlier seminal studies were also included when necessary to provide historical, mechanistic, or conceptual context. The review focuses was on alternative strategies that have shown effectiveness in preclinical or clinical settings to combat AMR in relation to bacterial pneumonia.ResultsEmerging strategies to tackle AMR in bacterial pneumonia involve several innovative approaches including stem cells, bacteriophage therapy, metal based nanoparticles (e.g., silver, copper, and gold). The adjunctive use of probiotics and herbal medicine has demonstrated potential in enhancing clinical outcomes and modulating host immunity. Moreover, gene editing technologies like CRISPR-CAS and various vaccination programs are being investigated for their roles in prevention and resistance management. While these methods show promise, many are still in the early stages of development and encounter challenges related to standardization, safety, and regulatory approval.ConclusionAlternative therapies present exciting possibilities for addressing AMR in bacterial pneumonia. However, to effectively translate these innovations into clinical practice, we need thorough research, international collaboration, and supportive policy frameworks. By combining these strategies with antimicrobial stewardship initiatives, we can help maintain antibiotic effectiveness and enhance patient outcomes.